Research Advances in Nucleic Acid Delivery System for Rheumatoid Arthritis Therapy - Xintong Zhang; Yanhong Liu; Congcong Xiao; Youyan Guan; Zhonggao Gao; Wei Huang (MDPI AG, 2023)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that affects the lives of nearly 1% of the total population worldwide. With the understanding of RA, more and more therapeutic drugs have been developed. However, lots of them possess severe side effects, and gene therapy may be a potential method for RA treatment. A nanoparticle delivery system is vital for gene therapy, as it can keep the nucleic acids stable and enhance the efficiency of transfection in vivo. With the development of materials science, pharmaceutics and pathology, more novel nanomaterials and intelligent strategies are applied to better and safer gene therapy for RA. In this review, we first summarized the existing nanomaterials and active targeting ligands used for RA gene therapy. Then, we introduced various gene delivery systems for RA treatment, which may enlighten the relevant research in the future.